Variation of Mineral Elemental Contents in the Root of Rheum tanguticum (Polygonaceae)-A Famous Tibetan Medicine from Different Habitat in Qinghai-Plateau - Li, Jinping; Han, Youji; Liu, Likuan; Li, Tiancai; Zhou, Guoying; Shang, Honglei; Chen, Guichen (Asian Journal of Chemistry, 2011)
The root of Rheum tanguticum and its soil, collected from 30 different habitats, were analyzed for 11 mineral elements, soil pH and soil organic material (SOM). Most elements vary over a wide range, depending on geo-environmental factors and different soil characteristics. The mineral element data were evaluated by multivariate methods, i.e., principal component analysis and correlation analysis to reveal the distribution pattern of elements in root and in soil. Effects of environmental factors (including altitude, longitude, latitude and four soil principal components) on the plant minerals were evaluated. Four principal components P1 (K and Ca factor), P2 (Cu factor), P3 (Mg factor), P4 (Zn and Se factor) of plant elements and four principal components S1 (Fe factor), S2 (Mg factor), S3 (SOM factor), S4 (Se factor) of soil were selected, which reflected the main pattern of minerals. It can be seen that P1 had positive correlation with S3 (p < 0.05) and latitude (p < 0.05); P2 showed positive correlation with S2 (p < 0.01), longitude (p < 0.05) and latitude (p < 0.05), but had negative correlation with altitude (p < 0.01); P3, P4 had no clear significant correlations with the environmental factors determined in this experiment. There are many inter-correlations between mineral elements in plant and inter-correlation between elements, pH and SOM in soil. Thus, it is important to consider the effects of different environmental factors and inter-correlation on the elemental distribution.